Promoting Multiple Representation in the TPACK Framework to Clarify the Acid-Base Species Problem-Solving - Mu'minah, Qonita; Mulyani, Sri (Hydrogen: Jurnal Kependidikan Kimia, 2026)
Oversimplifying chemical concepts to explain the invisible part is frequent in the concept of acid-base species determination. During school time, teachers frequently drill students to use straightforward formulas to prevent time-consuming calculations in calculating pH values. This attitude contributes to misleading problem-solving even among twenty-three preservice teachers at one of the educational universities in West Java, Indonesia. Therefore, the lecturer developed a learning strategy that uses the TPACK framework and multiple representations to clarify the misleading and prepare chemistry preservice teachers to overcome similar challenges in real-world situations. The multiple representations and misconceptions analysis was assigned to determine a suitable pedagogical strategy and identify appropriate technology. Quantitative assessments were used to measure changes in problem-solving approaches. It discovers that they have an excellent understanding of solving the acid-base problems using the conceptual approach, with increasing: 13.0% to 60.9% and 43.4% to 56.5%. However, some mathematical issues appear if the conditions are related to more complex acid-base scenarios, such as those related to buffer and hydrolysis regions. It is shown that the percentage of the conceptual approach usage decreases or remains constant: 69.6% to 45.7% and 43.4%, respectively. This shows that the symbolic level in chemistry learning is also linked to mathematical skills. As a consequence, chemistry preservice teachers must have a strong mathematical basic skills to solve problems correctly. Further study is also recommended in other chemistry subjects to get a broader view.